Properties on Micro Pre-Covering Map in Micro Topological Spaces - Stanley Roshan. S; P. Sathishmohan; K. Rajalakshmi; S. Mythili (Statistics, Optimization & Information Computing, 2025)
The basic objective of this research work is to introduce and investigate the properties of micro semi-continuous, micro pre-continuous, micro pre-irresolute map, micro pre-covering map.